A Novel Association of Polymorphism in the ITGA4 Gene Encoding the VLA-4 α4 Subunit with Increased Risk of Alzheimer's Disease - Vladimira Durmanova; Zuzana Parnicka; Juraj Javor; Gabriel Minarik; Lubomir Vrazda; Barbora Vaseckova; Karin Gmitterova; Maria Kralova; Jan Pecenak; Peter Filipcik; Ivana Shawkatova (Hindawi Limited, 2018)
Alzheimer's disease (AD) is the most prevalent cause of dementia in elderly people worldwide. Many studies support the hypothesis that the inflammation of the CNS contributes to the neurodegeneration and disease progression. The integrin molecule α4β1, also known as very late antigen 4 (VLA-4), belongs to adhesion molecules that activate the inflammatory process through the migration of immune cells into the CNS. Therefore, the objective of our study was to analyze the association between two polymorphisms located in the ITGA4 gene encoding the α4 subunit of VLA-4 and the risk of AD. 104 late-onset AD patients and 206 control subjects from Slovakia were genotyped for ITGA4 gene SNP polymorphism rs113276800 (−269C/A) and rs1143676 (+3061A/G). The same study cohorts were also genotyped for the APOE-ε4, which is a known genetic factor associated with increased risk of AD developing. ITGA4 polymorphism analysis revealed significantly higher frequency of the +3061AG carriers in AD group compared to the controls (P≤0.05). Following the APOE-ε4 stratification of study groups, the association remained significant only in APOE-ε4 noncarriers. Our study suggests a novel association of ITGA4 +3061A/G polymorphism with AD and its possible contribution to the disease pathology.